EXPLORING EDUCATIONAL VALUES OF MARYAM BINTI IMRAN THROUGH ISLAMIC INFORMATION LITERACY - Septiani, Rita; Arsyad, Junaidi; Budiman, Budiman (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
This study aims to explore the educational values exemplified by Maryam binti Imran and to analyze how these values can be internalized through the framework of Islamic Information Literacy. Grounded in a qualitative approach using literature review methodology, the research draws upon classical tafsir works, contemporary Islamic educational texts, and thematic Qur'anic exegesis. The primary data include authoritative Islamic texts such as Tafsir Al-Munir, Tafsir Ibnu Katsir, and Shahih Qashashil Qur’an, complemented by scholarly discourse on religious literacy and character formation. The findings reveal that Maryam embodies core Islamic values—spirituality, chastity, fortitude, and social responsibility—through her ability to receive, understand, evaluate, and act upon divine revelation. Her life serves as a model of effective Islamic information processing: she exercises discernment in distinguishing between divine truth and social stigma, demonstrates spiritual resilience in the face of severe trials, and maintains moral integrity despite public pressure. These values are not inherited passively but are cultivated through active engagement with authentic religious sources. The study concludes that Islamic Information Literacy is not merely a technical or academic skill, but a transformative tool that shapes faith-based character and ethical awareness. Incorporating Maryam’s example into the Islamic education curriculum can enhance students’ intellectual, emotional, and spiritual competencies, positioning her as a pedagogical model for values-based education in the modern era.